PENGARUH FLEXING DAN GAYA HIDUP MEWAH TERHADAP BRAND AWARENESS MELALUI PERSONAL BRANDING - Alika Rahmah; Zeffanya Raphael Wijaya (Jurnal Pijar, 2026)
This study analyzes the influence of flexing and luxurious lifestyles on brand awareness through personal branding on the TikTok platform, using Shella Saukia as a case study. A quantitative method with a causal design was used, involving 100 active TikTok users who were familiar with the @shellasaukia account. Data analysis used path analysis with SPSS and AMOS. The results showed that flexing has no significant effect on personal branding (t=1.719; p=0.086), while luxurious lifestyle has a significant effect (t=3.454; p=0.000). Personal branding has a significant effect on brand awareness (t=9.248; p=0.000). Simultaneously, flexing and luxurious lifestyle have significant effects on personal branding (F=49.87; R²=0.507) and on Brand awareness (F=59.04; R²=0.476). Personal branding acts as a partial mediator with an indirect effect of luxurious lifestyle of 0.269. These findings contribute to digital communication strategies on social media.